Discourse on Islamization of Perspective Science (Universitas Muhammadiyah Sidoarjo, 2017)
This paper aims to understand and hope about the Islamization of science perspective al Faruqi that disciplines are not regulated and programmed from the sky. Discipline is born from the matrix of a special worldview and hierarchically always subordinated to the worldview. The disciplines of science have no autonomous existence for themselves but evolve according to specific historical and cultural environments and have only a meaning in the world view which gives birth and evolves them. The division of knowledge into the present disciplines is a peculiar manifestation of Western civilization when formulating the problems at hand. For example, the discipline of orientalism was developed because the West regarded Islam as a problem to be studied, analyzed and dictated. Thus, accepting the division of disciplines according to Western epistemology as al Faruqi still does, is synonymous with subordinating the Islamic world-view to Western civilization.